2022
DOI: 10.1155/2022/4083494
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Admission to the Intensive Care Unit and Mortality of Critically Ill Adults: Systematic Review and Meta-analysis

Abstract: Delayed admission of patients to the intensive care unit (ICU) is increasing worldwide and can be followed by adverse outcomes when critical care treatment is not provided timely. This systematic review and meta-analysis appraised and synthesized the published literature about the association between delayed ICU admission and mortality of adult patients. Articles published from inception up to August 2021 in English-language, peer-reviewed journals indexed in CINAHL, PubMed, Scopus, Cochrane Library, and Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
2
12
0
1
Order By: Relevance
“…A study of 102 critically ill patients showed that a shortage of ICU beds (65.1%) and holdups in radiological examination (15.1%) were common reasons for delayed admission [ 27 ]. A meta-analysis conducted by Keikkas et al [ 28 ] found that the main reasons for delayed ICU admission were an increase in the demand for ICU beds due to population aging and miscommunication among physicians; this study also found that patients with delayed admission tended to be older and had more comorbidities. Similarly, a study that investigated the association between the timing of ICU admission and outcomes in patients with pneumonia demonstrated that the decision to admit a patient to the ICU was often limited by the patient’s age, comorbidities, and premorbid functional status [ 29 ].…”
Section: Discussionmentioning
confidence: 54%
“…A study of 102 critically ill patients showed that a shortage of ICU beds (65.1%) and holdups in radiological examination (15.1%) were common reasons for delayed admission [ 27 ]. A meta-analysis conducted by Keikkas et al [ 28 ] found that the main reasons for delayed ICU admission were an increase in the demand for ICU beds due to population aging and miscommunication among physicians; this study also found that patients with delayed admission tended to be older and had more comorbidities. Similarly, a study that investigated the association between the timing of ICU admission and outcomes in patients with pneumonia demonstrated that the decision to admit a patient to the ICU was often limited by the patient’s age, comorbidities, and premorbid functional status [ 29 ].…”
Section: Discussionmentioning
confidence: 54%
“…47,49,50 Delayed ICU admission is associated with higher mortality risk, suggesting potential improvements in resource allocation within the Western Cape healthcare system. 51,52 Furthermore, in the Western Cape, the median time to damage control surgery is 30.0 h. 47 Our study found that most deaths occurring between 4 and 24 h post injury occurred in the emergency unit, where the patient may be awaiting provision of critical care or pending transfer to higher levels of care, sub-surgical specialist, and/or theater. 11,53 These findings support the claim that delays in time from injury to definitive care are deleterious.…”
Section: Discussionmentioning
confidence: 67%
“…In the Western Cape, due to transfer to the tertiary or regional hospital the median time from injury to ICU admission is 17.3 h, compared to 5.4–7.0 h in other middle‐income countries 47,49,50 . Delayed ICU admission is associated with higher mortality risk, suggesting potential improvements in resource allocation within the Western Cape healthcare system 51,52 . Furthermore, in the Western Cape, the median time to damage control surgery is 30.0 h 47 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that delayed presentation to care was potentially detrimental. Other studies show that delayed admission to the ICU is associated with increased mortality; an observational study showed that each 1-hour increase in delay was associated with an adjusted 3% increase in odds of hospital mortality ( 34 , 35 ). In our cohort, NHW were older and with more comorbidities and we suspect this is why mortality was not different between NHW and patients from racial and ethnic minority groups.…”
Section: Discussionmentioning
confidence: 99%